What Do They Think? Families Share Benefits of an After-School Tutoring Program - Dr. Tammy Zilliox; Dr. Teresa L. Young (Educational Considerations, 2025)
There are many afterschool programs that provide tutoring services for K-8 elementary students. Although much research has been conducted on the benefits field experiences have for preservice teachers, and even more research on the impact family engagement has on student achievement, little research has been focused on how embedded field experiences benefit not only preservice teachers but also family engagement. The purpose of this study was to gather feedback from families whose children participated in an embedded field experience. Findings from this study highlighted the benefits of an embedded field experience in a university course for the university students’ literacy growth, the K-5 students they serve, and their families.
Keywords: literacy assessment; family engagement; pre-service teachers; after-school tutoring